Production characteristics of Small East African goats and their crosses with Anglo-Nubian and Alpine under station conditions in semi-arid 'Bugesera' region of eastern Rwanda - Murayi, T.; Sayers, A.R.; Wilson, R.T. (Arab Center for the Studies of Arid Zones and Dry Lands, 1987)
Discusses production characteristics of Small East African goats and their crosses with Anglo-Nubian and Alpine under semi-arid conditions in eastern Rwanda. Examines reproductive performance, growth, weight, mortality and productivity indices.